Low-molecular-weight hydroxyl-terminated polyethylene modified asphalt and preparation method thereof
By designing a 'hydrophobic backbone + terminal hydroxyl' structure in low molecular weight polyethylene modified asphalt, the compatibility and segregation problems of polyethylene modified asphalt are solved, the processing technology is simplified, energy consumption and harmful gas emissions are reduced, and the stability and performance of asphalt are improved.
Patent Information
- Application Number
- CN202511037188.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-11-04
AI Technical Summary
Existing polyethylene-modified asphalt suffers from poor compatibility, easy segregation, high construction energy consumption, and harmful gas emissions, making it difficult to meet the needs of modern roads.
Low molecular weight hydroxyl-terminated polyethylene (HO-PE) is used to modify asphalt. Through the 'hydrophobic backbone + terminal hydroxyl' structural design, hydrogen bonds are formed between the terminal hydroxyl groups and the polar components of asphalt. Combined with the van der Waals forces of the hydrophobic backbone and the non-polar components, a dual match between polar and non-polar components is achieved, simplifying the processing technology and reducing energy consumption.
It improves the high-temperature stability and low-temperature crack resistance of asphalt, reduces construction energy consumption and harmful gas emissions, enhances the compatibility and stability of modified asphalt, avoids water damage, and achieves synergistic optimization of multi-dimensional performance.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of modified materials, in particular to a low-molecular-weight hydroxyl-terminated polyethylene modified asphalt and a preparation method thereof. BACKGROUND
[0002] Asphalt, as an important road paving material, its performance greatly affects the quality and service life of the road. With the rapid development of transportation industry, the road is facing more complex working conditions such as heavier load, higher traffic volume and seasonal temperature change, which puts forward higher requirements for the performance of road asphalt material. The traditional asphalt material is prone to softening and flowing at high temperature, and becomes brittle at low temperature, resulting in problems such as rutting and cracking of the road surface, which is difficult to meet the use requirements of modern roads.
[0003] Polyethylene has low price and good high-temperature resistance, low-temperature resistance and chemical stability. Combining polyethylene with asphalt can effectively improve the softening point of asphalt, reduce its temperature sensitivity, and thus improve the high-temperature rutting resistance and low-temperature cracking resistance of asphalt. However, the current polyethylene modified asphalt still has some problems, such as poor storage stability, and polyethylene and asphalt are prone to phase separation, which leads to the decline of the performance of the modified asphalt, limiting its wide application. In addition, polyethylene and asphalt have significant differences in physical properties such as molecular weight, density and solubility parameter, resulting in poor compatibility between them, which is prone to segregation during production, hot storage and use. In summary, although polyethylene can improve the performance of asphalt and reduce the modification cost, there are two significant problems in its practical application: ① During construction, the high-temperature viscosity of polyethylene modified asphalt increases, which easily causes energy consumption and harmful gas emission; ② The poor compatibility between asphalt and polyethylene leads to poor modification effect due to segregation of the system.
[0004] Polyvinyl alcohol (PVA) modified asphalt can improve the compatibility problem to some extent. PVA can form hydrogen bonds with the polar components (such as asphaltene) of asphalt through a large number of hydroxyl groups (-OH) in the molecular chain, which can improve the high-temperature stability and adhesion of asphalt. The typical method is to blend PVA powder with molten asphalt at high temperature (>180℃), supplemented by a compatibilizer (such as a silane coupling agent) to improve the dispersibility. However, PVA has certain limitations: ① Strong hydrophilicity: PVA has strong hygroscopicity, and the modified asphalt is prone to adhesion loss and poor water damage resistance due to water absorption; ② High processing energy consumption: PVA has a high melting point (~230℃), which requires long-time high-temperature shearing, which increases the risk of asphalt aging; ③ Compatibility depends on additives: 5%-10% of compatibilizers need to be added, which increases the cost and complicates the process. Therefore, it is necessary to develop a new modifier to solve the above technical problems. SUMMARY
[0005] The present application aims to provide a low molecular weight end hydroxyl polyethylene modified asphalt and a preparation method thereof to solve the problems in the prior art.
[0006] To solve the above technical problems, the present application provides the following technical solutions: a low molecular weight end hydroxyl polyethylene modified asphalt and a preparation method thereof, which comprises the following preparation steps: (1) adding a nitrogen-containing heterocyclic organic compound and an organic solvent in a container, stirring to add an aniline substance, dropping a catalyst, heating, refluxing, adding a precipitant, filtering and drying to obtain a ligand; (2) placing the ligand obtained in step (1) in a container, adding an iron complex, vacuumizing with argon, stirring to add a reaction solvent, standing, filtering and washing to obtain a catalyst; (3) placing the catalyst prepared in step (2) in a container, adding a solvent to configure a solution, adding a cocatalyst, introducing ethylene gas, controlling the temperature and stirring to obtain a product A; (4) extracting and rotary evaporating the product A obtained in step (3) to obtain a product B; (5) placing the product B in a container, dissolving by adding a solvent, controlling the temperature, stirring, dropping a borohydride reagent, heating and reacting, cooling, dropping an oxidizing agent, stirring, adding a precipitant, filtering and washing, and vacuum drying to obtain a modifier; (6) taking a base asphalt, heating, adding the modifier prepared in step (5), stirring and drying, and continuously stirring to obtain a low molecular weight end hydroxyl polyethylene modified asphalt.
[0007] Further, the nitrogen-containing heterocyclic organic compound in step (1) is 2,6-diacetylpyridine, and the molar mass is 5-15 mmol; the organic solvent in step (1) is dichloromethane; and the aniline substance is 2,4-methylaniline or 4-methoxy-2-methylaniline, and the molar mass is 10-30 mmol.
[0008] Further, the catalyst in step (1) is formic acid, and the volume is 0.1-0.2 ml; and the precipitant in step (1) is anhydrous methanol, and the volume is 450-550 ml.
[0009] Further, the iron complex in step (2) is ferrous chloride tetrahydrate, and the molar mass ratio of the iron complex to the ligand is 1:9.5-12; and the reaction solvent in step (2) is tetrahydrofuran, and the volume is 30-50 mL.
[0010] Further, the solvent in step (3) is cyclohexane; the concentration of the configured solution is 0.5-1.5 μmol / mL; and the cocatalyst in step (3) is MAO (methylaluminoxane), and the volume is 3-8 ml.
[0011] Further, the step (3) introduces ethylene with purity of 99.999%; the heating temperature is 60-120℃; and the rotating speed is 300-800r / min.
[0012] Further, the step (5) produces product B with mass of 3-8g; the solvent is tetrahydrofuran with volume of 80-120ml; the boron hydride reagent is borane tetrahydrofuran complex with volume of 15-25ml; and the oxidizing agent is hydrogen peroxide / sodium hydroxide aqueous solution mixture with volume of 450-550ml, and the volume ratio of the two is 10:1.
[0013] Further, the step (6) uses SK90 as the matrix asphalt; and the modifier content is 1-5wt%.
[0014] Further, a low molecular weight hydroxyl-terminated polyethylene modified asphalt is prepared by the method.
[0015] Compared with the prior art, the present application has the following beneficial effects: Firstly, the low molecular weight hydroxyl-terminated polyethylene (HO-PE) prepared by the present application adopts the structure of "hydrophobic main chain + terminal hydroxyl group", and the terminal hydroxyl group can form hydrogen bonds with the polar components (such as the hydroxyl group and the carbonyl group of asphaltene) in asphalt, which makes up for the compatibility defects caused by the weak van der Waals force between the traditional polyethylene (PE) and the polar components in asphalt; at the same time, the hydrophobic main chain forms good van der Waals force with the non-polar saturated components and aromatic components in asphalt, realizing the dual matching with the "polar-non-polar" components in asphalt and greatly reducing the interfacial tension between the two phases. This "moderate polarity" design has more advantages than the strong hydrophilicity of polyvinyl alcohol (PVA) - PVA is easy to form strong hydrogen bonds with water due to the large number of hydroxyl groups in the molecular chain, resulting in a decrease in the adhesive force of modified asphalt after water absorption, while HO-PE only contains a small amount of hydroxyl groups at the end, and the interaction with water is limited, effectively avoiding the water damage defect.
[0016] Then, the low molecular weight and low melting point of HO-PE make it can be quickly dispersed by simple magnetic stirring at the conventional asphalt mixing temperature (150-160℃), avoiding the high temperature and long time shearing required by PVA or the dynamic vulcanization process commonly used in traditional polyethylene modification, which not only reduces the processing energy consumption and the risk of asphalt aging, but also simplifies the process and reduces the cost due to the good compatibility without the need for additional compatibilizers.
[0017] Further, the simplification of the process and the increase in compatibility further promote the overall improvement of the performance of the modified asphalt. From the perspective of thermodynamic stability, the terminal hydroxyl groups of HO-PE adjust the solubility parameter matching degree with the asphalt, reduce the chemical potential difference of the two phases, and make the system more stable; at the same time, the terminal hydroxyl groups form "physical crosslinking points" with the hydrogen bonds of the polar components of the asphalt, inhibit the aggregation and migration of HO-PE molecules, and effectively solve the problem of easy segregation of traditional PE modified asphalt. In addition, the low molecular weight characteristics of HO-PE make it more free to move at high temperatures, which can effectively reduce the internal friction resistance of the modified asphalt, thereby reducing the high-temperature viscosity of the overall system, achieving the flow required for construction at a lower temperature, reducing energy consumption and harmful gas emissions during the construction process, and achieving energy saving and emission reduction.
[0018] In summary, the controllable design of the polarity of the material structure used in the present application is the basis for subsequent process simplification and performance improvement, in which the low molecular weight characteristics support the realization of a low-temperature and efficient process, and the optimization of the process further guarantees the improvement of compatibility and stability of performance, ultimately achieving the synergistic optimization of multi-dimensional performance at low cost, forming a virtuous cycle of "structural innovation-process simplification-performance improvement-cost controllable". DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0020] In order to more clearly illustrate the method provided by the present application, the following embodiments are described in detail. In the following embodiments, the test methods of various indexes of low molecular weight hydroxyl-terminated polyethylene modified asphalt are as follows: Top softening temperature: GB / T15180-2010 Bottom softening temperature: GB / T15180-2010 Overall area: JTGE20-2011 Peeling area: JTGE20-2011 Peeling rate: Peeling area / Overall area*100% Adhesion grade: JTGE20-2011 Embodiment 1 (1) In a round bottom flask, 10 mmol of 2,6-diacetylpyridine was added, dissolved in dichloromethane, 20 mmol of 2,4-methylaniline was added by stirring, 0.15 ml of formic acid was added dropwise, the temperature was raised to 50°C, and refluxed for 48 h, 500 ml of anhydrous methanol was added, precipitated, filtered, and dried to obtain the ligand; (2) 10.5 mmol of the ligand obtained in step (1) was placed in a two-neck flask, 1 mmol of ferrous chloride tetrahydrate was added, vacuumed with argon, 40 ml of tetrahydrofuran was added by stirring, reacted for 1 h, and then filtered under argon, washed with anhydrous ether, and vacuum dried to obtain the catalyst; (3) The catalyst prepared in step (2) was placed in a beaker, a 1 μmol / mL solution was prepared by adding cyclohexane, 5 ml of MAO was added, pure ethylene gas with a purity of 99.999% was introduced, the temperature was controlled at 90°C, and the stirring speed was 500 r / min, and the product A was obtained by reaction; (4) The product A obtained in step (3) was placed in an extractor, extracted for 8 h, and rotary evaporated to obtain the product B; (5) 5 g of the product B was placed in a container, 100 ml of tetrahydrofuran was added, stirred at 40°C for 1 h, 20 ml of borane tetrahydrofuran complex was added dropwise, the temperature was raised to 60°C, reacted for 3 h, cooled to room temperature, 500 ml of a mixture of hydrogen peroxide / sodium hydroxide aqueous solution with a volume ratio of 10:1 was added dropwise, stirred for 2 h, methanol was added, filtered and washed, and vacuum dried at 50°C for 12 h to obtain the modifier; (6) The base asphalt SK90 was heated to 150°C, 3 wt% of the modifier prepared in step (5) was added, stirred at 800 r / min for 15 min, placed in an oven, heated to 160°C for 10 min, and then continued to stir at 800 r / min for 10 min to obtain the low molecular weight hydroxyl-terminated polyethylene modified asphalt.
[0021] Example 2 (1) In a round bottom flask, 15 mmol of 2,6-diacetylpyridine was added, dissolved in dichloromethane, 30 mmol of 2,4-methylaniline was added by stirring, 0.20 ml of formic acid was added dropwise, the temperature was raised to 50°C, and refluxed for 48 h, 550 ml of anhydrous methanol was added, precipitated, filtered, and dried to obtain the ligand; (2) 12 mmol of the ligand obtained in step (1) was placed in a two-neck flask, 1 mmol of ferrous chloride tetrahydrate was added, vacuumed with argon, 50 ml of tetrahydrofuran was added by stirring, reacted for 1 h, and then filtered under argon, washed with anhydrous ether, and vacuum dried to obtain the catalyst; (3) The catalyst prepared in step (2) was placed in a beaker, and cyclohexane was added to prepare a solution with a concentration of 1.5 μmol / mL. Then, 8 ml of MAO was added, and ethylene gas with a purity of 99.999% was introduced. The temperature was controlled at 120°C, and the stirring speed was 800 r / min. The product A was obtained by reaction; (4) The product A obtained in step (3) was placed in an extractor, and extracted for 8 h. Then, rotary evaporation was performed to obtain the product B; (5) 5 g of the product B was placed in a container, and 120 ml of tetrahydrofuran was added. The mixture was stirred at 40°C for 1 h. Then, boro-tetrahydrofuran complex 25 mL was added dropwise. The temperature was increased to 60°C, and the reaction was performed for 3 h. After cooling to room temperature, a mixture of hydrogen peroxide / sodium hydroxide aqueous solution with a volume ratio of 10:1 was added dropwise. The mixture was stirred for 2 h. Then, methanol was added. After filtration and washing, vacuum drying was performed at 50°C for 12 h to obtain the modifier; (6) The base asphalt SK90 was heated to 150°C. Then, 5 wt% of the modifier prepared in step (5) was added, and the mixture was stirred at 800 r / min for 15 min. The mixture was placed in an oven, and the temperature was controlled at 160°C for 10 min. Then, the stirring was continued at 800 r / min for 10 min to obtain the low-molecular-weight hydroxyl-terminated polyethylene modified asphalt.
[0022] Example 3 (1) 5 mmol of 2,6-diacetylpyridine was added to a round-bottom flask, and dichloromethane was added to dissolve the 2,6-diacetylpyridine. Then, 10 mmol of 2,4-methylaniline was added, and 0.10 ml of formic acid was added dropwise. The temperature was increased to 50°C, and the mixture was refluxed for 48 h. Then, 550 ml of anhydrous methanol was added. After precipitation, filtration and drying, the ligand was obtained; (2) 9.5 mmol of the ligand obtained in step (1) was placed in a two-neck flask, and 1 mmol of ferrous chloride tetrahydrate was added. The mixture was vacuumed by argon gas. Then, 30 ml of tetrahydrofuran was added, and the mixture was stirred for 1 h. After standing, the mixture was filtered under argon gas, washed with anhydrous ether, and vacuum dried to obtain the catalyst; (3) The catalyst prepared in step (2) was placed in a beaker, and cyclohexane was added to prepare a solution with a concentration of 0.5 μmol / mL. Then, 3 ml of MAO was added, and ethylene gas with a purity of 99.999% was introduced. The temperature was controlled at 60°C, and the stirring speed was 300 r / min. The product A was obtained by reaction; (4) The product A obtained in step (3) was placed in an extractor, and extracted for 8 h. Then, rotary evaporation was performed to obtain the product B; (5) 3 g of the product B was placed in a container, and 80 ml of tetrahydrofuran was added. The mixture was stirred at 40°C for 1 h. Then, boro-tetrahydrofuran complex 15 mL was added dropwise. The temperature was increased to 60°C, and the reaction was performed for 3 h. After cooling to room temperature, a mixture of hydrogen peroxide / sodium hydroxide aqueous solution with a volume ratio of 10:1 was added dropwise. The mixture was stirred for 2 h. Then, methanol was added. After filtration and washing, vacuum drying was performed at 50°C for 12 h to obtain the modifier; (6) Take the base asphalt SK90, heated to 150°C, add 1wt% of the modifier prepared in step (5), 800r / min stirring 15min, put into the oven, 160°C, 10min, then 800r / min continue to stir 10min, to get low molecular weight terminal hydroxyl polyethylene modified asphalt.
[0023] Comparative Example 1 (1) Take the base asphalt SK90, heated to 150°C, add 3wt% of the PVA purchased on the market as a modifier, 800r / min stirring 15min, put into the oven, 160°C, 10min, dry, then 800r / min continue to stir 10min, to get modified asphalt.
[0024] Comparative Example 2 (1) Take the base asphalt SK90, heated to 150°C, add 5wt% of the PVA purchased on the market as a modifier, 800r / min stirring 15min, put into the oven, 160°C, 10min, dry, then 800r / min continue to stir 10min, to get modified asphalt.
[0025] Comparative Example 3 (1) Take the base asphalt SK90, heated to 150°C, add 3wt% of the EPE (end epoxy polyethylene) purchased on the market as a modifier, 800r / min stirring 15min, put into the oven, 160°C, 10min, dry, then 800r / min continue to stir 10min, to get modified asphalt.
[0026] Comparative Example 4 (1) Take the base asphalt SK90, heated to 150°C, add 3wt% of the PE (polyethylene) purchased on the market as a modifier, 800r / min stirring 15min, put into the oven, 160°C, 10min, dry, then 800r / min continue to stir 10min, to get modified asphalt.
[0027] Effect Example The performance analysis results of the modified asphalt using the examples 1 to 3 and the comparative examples 1 to 4 of the present application are given in the following Table 1.
[0028] From the data analysis of the examples and comparative examples, it can be seen that the low molecular weight hydroxyl-terminated polyethylene (HO-PE) prepared by the present application adopts a "hydrophobic main chain + terminal hydroxyl" structure, the terminal hydroxyl can form a hydrogen bond with the polar components (such as the hydroxyl and carbonyl of asphaltene) in asphalt, which makes up for the compatibility defects caused by the weak van der Waals force between the traditional polyethylene (PE) and the polar components in asphalt; at the same time, the hydrophobic main chain forms a good van der Waals force with the non-polar saturated components and aromatic components in asphalt, realizing the dual matching with the "polar-non-polar" components in asphalt, and greatly reducing the interfacial tension between the two phases. This "moderate polarity" design has more advantages than the strong hydrophilicity of polyvinyl alcohol (PVA) - PVA is easy to form strong hydrogen bonds with water due to the large number of hydroxyl groups in the molecular chain, resulting in a decrease in the adhesive force of modified asphalt after water absorption, while HO-PE only contains a small amount of hydroxyl groups at the end, and the action with water is limited, effectively avoiding the water damage resistance defect; from the point of view of thermodynamic stability, the terminal hydroxyl group of HO-PE adjusts the solubility parameter matching degree with asphalt, reduces the chemical potential difference between the two phases, and makes the system more stable; at the same time, the hydrogen bond interaction between the terminal hydroxyl group and the polar components in asphalt forms a "physical crosslinking point", inhibits the aggregation and migration of HO-PE molecules, and effectively solves the problem of easy segregation of traditional PE modified asphalt.
[0029] The modified asphalt prepared by the present application has the advantages of simple process, controllable cost, energy saving and emission reduction, strong water damage resistance, good stability, and achieves the synergistic optimization of multi-dimensional performance, forming a virtuous cycle of "structural innovation-process simplification-performance improvement-cost controllability".
[0030] It is apparent for those skilled in the art that the present application is not limited to the details of the above exemplary embodiments, and the present application can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting, and the scope of the present application is defined by the appended claims rather than the above description, and all changes falling within the meaning and scope of the equivalent elements of the claims should be included in the present application. Any mark in the claims should not be regarded as limiting the involved claims.
Claims
1. A low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method, characterized in that, The preparation steps include the following: (1) Add nitrogen-containing heterocyclic organic compounds and organic solvents to a container, stir and add aniline substances, add catalyst dropwise, heat up, reflux, add precipitant, filter and dry to obtain ligands; (2) Place the ligand obtained in step (1) in a container, add the iron complex, evacuate with argon gas, stir and add the reaction solvent, let stand, filter, wash and dry to obtain the catalyst; (3) Place the catalyst prepared in step (2) in a container, add solvent to prepare a solution, add a co-catalyst, introduce ethylene gas, and stir while controlling the temperature to obtain product A; (4) Extract and rotary evaporate the product A obtained in step (3) to obtain product B; (5) Place product B in a container, add solvent to dissolve it, control the temperature, stir, add boronizing agent dropwise, heat up to react, cool, add oxidant dropwise, stir, add precipitant, filter and wash, vacuum dry to obtain modifier; (6) Take the base asphalt, heat it, add the modifier prepared in step (5), stir, dry, and continue stirring to obtain low molecular weight hydroxyl-terminated polyethylene modified asphalt.
2. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The nitrogen-containing heterocyclic organic compound in step (1) is 2,6-diacetylpyridine with a molar mass of 5-15 mmol; the organic solvent in step (1) is dichloromethane; and the aniline substance is 2,4-methylaniline or 4-methoxy-2-methylaniline with a molar mass of 10-30 mmol.
3. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The catalyst in step (1) is formic acid, with a volume of 0.1~0.2 ml; the precipitant in step (1) is anhydrous methanol, with a volume of 450~550 ml.
4. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The iron complex in step (2) is ferrous chloride tetrahydrate, and its molar mass ratio with the ligand is 1:9.5~12; the reaction solvent in step (2) is tetrahydrofuran, and the volume is 30~50mL.
5. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The solvent in step (3) is cyclohexane; the concentration of the prepared solution is 0.5~1.5μmol / mL; the co-catalyst in step (3) is MAO (methylaluminoxane), with a volume of 3~8ml.
6. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, In step (3), the ethylene purity is 99.999%; the heating temperature is 60~120℃; and the rotation speed is 300~800r / min.
7. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The mass of product B in step (5) is 3~8g; the solvent is tetrahydrofuran, with a volume of 80~120ml; the boronizing agent is a boran tetrahydrofuran complex, with a volume of 15~25ml; the oxidant is a mixture of hydrogen peroxide / sodium hydroxide aqueous solution, with a volume of 450~550ml and a volume ratio of 10:
1.
8. The low molecular weight hydroxyl-terminated polyethylene modified asphalt and its preparation method according to claim 1, characterized in that, The base asphalt in step (6) is SK90; the content of the modifier is 1~5wt%.
9. A low molecular weight, hydroxyl-terminated polyethylene-modified asphalt, characterized in that, The modified asphalt is prepared by the method according to any one of claims 1 to 8.